Facilitated Transitions to Postpartum Primary Care and Mental Health Care Services - Julia C. P. Eddelbuettel; Alaka Ray; Pichliya Liang; Kaitlyn E. James; Ishani Ganguli; Mark A. Clapp; Jessica L. Cohen (JAMA Network Open, 2026)
Importance Postpartum anxiety and depression are common complications of pregnancy but often go untreated. Primary care offers an opportunity to provide mental health care services after the immediate postpartum period, but it is underused, in part because of ineffective transitions after delivery from obstetric care to primary care. Objective To evaluate whether an intervention to improve transitions from obstetric care to postpartum primary care is associated with increased mental health care utilization for individuals with mood and anxiety disorders. Design, Setting, and Participants This ad hoc secondary analysis of an individual-level, 1:1 stratified randomized clinical trial was conducted from November 3, 2022, to October 11, 2023, at a hospital-based obstetric clinic and 5 community-based outpatient obstetric clinics affiliated with a large academic medical center in Massachusetts. Participants included pregnant or postpartum individuals with diagnosed anxiety, depressive mood disorder, or both. Analyses were conducted from June 2024 to February 2026. Intervention A behavioral economics–informed intervention designed to reduce administrative burdens and information gaps that impede postpartum primary care engagement. Main Outcomes and Measures Outcomes were derived from both administrative records and patient survey data. Outcomes included postpartum primary care utilization, receipt of mental health care services (screening, counseling, prescriptions, and referrals) within primary care, and overall receipt of mood medication or mental health care services. Intent-to-treat linear regression models were used to evaluate the association between the intervention and study outcomes, with results presented as percentage point (pp) differences adjusted for the 2 covariates used for randomization strata (whether the patient received prenatal care at the main hospital obstetric center or at one of the clinics and whether they had a primary care practitioner visit in the last 3 years). Results A total of 266 trial participants with diagnosed anxiety, depressive mood disorder, or both were included in the analysis. The sample mean (SD) age was 33.7 (4.7) years, and 68 participants (25.6%) reported their mental health as fair or poor. Administrative records indicated that the intervention vs standard care was associated with increased mental health care service receipt in primary care, including an 18.3 pp difference (33.3% vs 15.6% ; P < .001) in primary care visits that included mood screening and a 15.9 pp difference (39.9% vs 24.2% ; P = .01) in primary care visits that included counseling or planning for mental health care. Differences in primary care–provided mental health care services were also found in participant surveys for the intervention vs control groups, including 12.8 pp greater participant-reported mental health prescriptions and referrals through primary care (23.2% vs 10.1% ; P = .03). No differences were found between the intervention and control groups for frequency of mood medication prescription (53.7% vs 47.7%; adjusted between-group difference, 6.0 pp; P = .44) or receipt of mental health care specialist services (48.8% vs 53.9%; adjusted between-group difference, −4.6 pp; P = .55). However, participant-reported receipt of mood medication in the subsample with diagnosed depression differed by 24.2 pp in the intervention vs control groups (78.0% vs 53.7%; P = .02). Conclusions and Relevance This study found that supported transitions to postpartum primary care may improve receipt of primary care–provided mental health care services. This relatively low-cost intervention may be one strategy to facilitate ongoing access to mental health care supports and treatments beyond the immediate postpartum period. Trial Registration ClinicalTrials.gov Identifier: NCT05543265